Efektivitas Konseling Kelompok dengan Teknik REBT untuk Mereduksi Bullying pada Siswa di Sekolah - Siti Konaah; Nofia Lolita; Zakia Rahmadania; Galuh Nabila Audry Rahmania; Ratna Sari Dewi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Bullying is a serious problem in the educational environment that has a negative impact on the psychological, academic, and social aspects for victims. This study aims to evaluate the effectiveness of group counseling services using the Rational Emotive Behavior Therapy (REBT) approach in reducing bullying behavior in schools. This research applied the literature study method by analyzing 21 relevant journals in the period 2020-2024. The research findings indicate that group counseling using REBT is effective in helping victims of abuse deal with irrational thought patterns, improve emotion regulation skills, and build self-confidence. Rational thinking methods, behavioral techniques, and role-playing in REBT proved effective in reducing bullying tendencies and improving students' psychological well-being. In addition, group dynamics in counseling provide social support that contributes to positive changes in student behavior. Therefore, the REBT approach in group counseling services is suggested as an effective strategy to address the effects of bullying and create a safer and more supportive school environment.